Defects of the Lamina Cribrosa in High Myopia and Glaucoma - Miki, Atsuya (PLoS One, 2015)
PURPOSE: We evaluated the prevalence and characteristics of the defects of the lamina cribrosa (LC) in high myopia and glaucoma, and compared them with control eyes using swept-source optical coherence tomography (SS-OCT). METHODS: One hundred fifty-nine eyes of 108 participants were divided into four subgroups; high myopia with glaucoma (MG, 67 eyes of 46 subjects), glaucoma without high myopia (G, 22 eyes of 13 subjects), high myopia without glaucoma (M, 35 eyes of 29 subjects), and a control group with neither glaucoma nor high myopia (C, 35 eyes of 20 subjects). The LC defects were identified and located using a standardized protocol in serial horizontal OCT scans. The prevalence rates of the defects were compared among the groups. Demographic and ocular factors were compared between eyes with and without defects. RESULTS: LC defects were observed in one eye (0.03%) in the C group, 8 eyes (22.9%) in the M group, 11 eyes (50%) in the G group, and 28 eyes (41.8%) in the MG group. The prevalence rates of the defects differed significantly among the groups (P = 0.0009). Most eyes with defects in the G and MG groups (79.5%) had damage in the corresponding visual hemifields. Other factors such as visual acuity, intraocular pressure, axial length, refractive error, disc ovality, or parapapillary atrophy area did not differ significantly between eyes with and without LC defects. CONCLUSIONS: High myopia and glaucoma significantly increased the risk of LC damage. The LC damage in non-glaucomatous highly myopic eyes may at least partly explain the increased risk of developing glaucoma in myopic eyes.